Response of calcium carbonate nanoparticles in hydrophobic solvent to pressure, temperature, and water - Dini,D; Bodnarchuk,MS; Heyes,DM; Breakspear,A; Chahine,S; Edwards,S (Journal of Physical Chemistry C, 2015)
Molecular Dynamics (MD) simulations of surfactant-stabilized calcium carbonate, CaCO3, nanoparticles in hydrophobic solvent have been carried out to characterize their response to changes in temperature (T) and pressure (P), and also their interaction with trace water and water droplets. The response to increasing temperature and pressure is sensitive to the type of model surfactant, with the sulfonate-stabilized particle, which is the most spherical, showing a weak temperature-pressure dependence, while the sulfurized alkyl phenol (SAP) and salicylate-stabilized particles distort into a more spherical shape with increasing temperature and pressure. The atom-atom radial distribution functions of the core ions reveal consolidation of the calcium carbonate structure with increasing temperature and pressure. The simulations show that the nanoparticles adsorb onto the surface of water droplets through a water bridge transitional mechanism, in agreement with evidence from experimental studies. In the case of the sulfonate surfactant particle, only, a number of surfactant molecules detached from the calcium carbonate core and transferred to the surface of the water droplet. Consequently this type of particle had the greatest interaction with and affinity for water which may explain its rapid neutralization characteristics observed in experiments. The detachment free energy of the sulfonate obtained by potential of mean force (PMF) calculations was the largest of the three, which is consistent with the core being more embedded in the water and less well stabilised on returning to the hydrophobic medium. The salicylate nanoparticle had about half the detachment free energy, which could give rise to a more dynamic equilibrium of attached-to-detached states for this class of nanoparticle.